Epidemiology of injuries sustained in professional Australian netball: A three season cohort study - Toohey, L. A.; Antcliff, A.; Drew, M. K.; Wells, F.; Saunders, N.; Piromalli, L. E.; West, S.; White, S.; Fox, A. S. (Journal of Science and Medicine in Sport, 2022)
Objectives: To report the medical attention and time-loss injury epidemiology of Australia's premier netball competition. Design: Descriptive epidemiological study. Methods: One-hundred and nineteen players in the Suncorp Super Netball league were under surveillance during three consecutive seasons (2017-2019), inclusive of pre-, in-, and post- season phases. Medical attention injuries were recorded by medical personnel, and additionally sub-categorised according to time loss. Injury incidence rates (IIR) and injury burden were calculated per 365 player contract days, with differences between season and season phase IIRs compared using negative binomial generated incidence rate ratios (IRR). Results: Eight hundred and sixty-six medical attention injuries and 393 time-loss injuries were recorded. The majority of the players had multiple ( 2) medical attention (n = 92; 77.3%) and time-loss (n = 75, 63.0%) injuries reported. The ankle (n = 181; 20.9%), knee (n = 136; 15.7%) and foot (n = 98; 11.3%) were the body sites with the most frequently reported medical attention injuries. Overall, there was a comparable injury incidence rate between the pre-season and in-season periods (IRR = 1.13, 95%CI = 0.98 1.30, p = 0.0842), although variation in the injury burden was identified. Ankle tendon injuries (23.5 days absence) and knee joint injuries (44.9 days absence) the most burdensome injuries in the pre-season and in-season periods respectively. Conclusions: Lower limb injuries are the most frequent in professional level netball. Knee and ankle injuries are the most burdensome overall, however the type of injuries with a high burden vary between pre- and in-season periods. Time-loss, non-time loss and subsequent injuries are prominent in professional level netball.